Clinical significance of serum high sensitive C-reactive protein/albumin ratio in primary prostate biopsy - Chen, Xinyang; Li, Yu; Li, Gang; Zhang, Xuefeng; Xie, Gansheng; Huang, Yuhua; Yin, Huming (Frontiers in Oncology, 2024)
The purpose of this study was to investigate the clinical significance of serum high sensitive C-reactive protein/albumin ratio in primary prostate biopsy. Methods: Retrospective analysis was done on the clinical data of 1679 patients who had their first transrectal or perineal prostate biopsy at our stitution from 2010 to 2018. Prostate cancer (PCa) and benign prostatic hyperplasia (BPH) were the pathologic diagnoses in 819 and 860 cases, respectively. A comparison was made between the HAR differences between PCa and BPH patients as well as the positive prostate biopsy rate differences between groups with increased and normal HAR. The results of the prostate biopsy were examined using logistic regression, and a model for predicting prostate cancer was created. The receiver characteristic curve (ROC) was used to determine the model's prediction effectiveness. The clinical models integrated into HAR were evaluated for their potential to increase classification efficacy using net reclassification improvement(NRI)and integrated discrimination improvement(IDI). According to the Gleason score (GS) categorization system, prostate cancer patients were separated into low, middle, and high GS groups. The differences in HAR between the various groups were then compared. The prevalence of high GSPCa and metastatic PCa in normal populations and the prevalence of higher HAR in prostate cancer patients were compared using the chi-square test. Result: Patients with PCa had a median HAR (upper quartile to lower quartile) of 0.0379 (10 -3 ), patients with BPH had a median HAR (0.0137 (10 -3 )), and the difference was statistically significant (p<0.05). Patients with increased HAR and the normal group, respectively, had positive prostate biopsy rates of 52%(435/839)and 46%(384/840), and the difference was statistically significant